CONVERSATIONAL IMPLICATURE: TALKSHOW IN OPRAH WINFREY NETWORK - Astrid Astrid; Faidah Yusuf; Jumharia Djamereng (Universitas Islam Negeri Sunan Gunung Djati, 2021)
This study is to determine the various forms of conversational implicature and their function on the talk show Oprah Winfrey Network's SuperSoul Sunday Program. The data were evaluated descriptively qualitatively. The results show that three types of data classified as generalized conversational implicature and eleven types of data classified as particularized conversational implicature, depending on the utterance. Each host has a unique personality and circumstance, which contributes to defiance of the dictum. By floating the maxim, the speaker inferred meaning through his or her justifications, which either too brief or too detailed. As a result, the speaker delivered an irrelevant and ambiguous speech in response to the interlocutor. In conclusion, this implicature discovered the representational, directive, expressive, and declarative functions of utterances.Keywords: Implicature, Conversational Implicature, Talkshow, Floating The Maxim